Determinants of Credit Default in Banking in Nigeria - Chiamaka, Achebe (International Journal of Modern Risk Management, 2023)
Purpose: The aim of the study was to examine the determinants of credit default in banking in Nigeria. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: The determinants of credit default in Nigerian banking encompass a range of factors, including economic stability, regulatory oversight, risk management practices, loan portfolio quality, and macroeconomic conditions. Addressing these factors is crucial for banks to effectively manage credit risk and reduce the likelihood of credit defaults. Unique Contribution to Theory, Practice and Policy: Agency Theory, Pecking Order Theory and Information Asymmetry Theory may be used to anchor future studies on the examining determinants of credit default in banking in Nigeria. banks should initiate financial literacy programs for borrowers to improve their understanding of financial products and responsibilities. Regulators should encourage the adoption of advanced credit risk assessment models and provide guidelines on best practices in risk management.